Aristotle and Pedagogical Ethics - Kakkori, Leena; Huttunen, Rauno (Paideusis, 2007)
The teacher’s pedagogical ethics refers to the Kantian maxims that a teacher is obliged to follow. One could provide a list of the most crucial maxims that a teacher must absolutely not violate. We surely need these Kantian maxims in the teachers’ pedagogical ethics, although they tell us very little about the properties that good and moral teachers should possess. In teacher education we must of course elaborate on the ethical code of the teacher (maxims), but we must also consider the properties of a morally good teacher. A good source in endeavouring to find these properties is the book Aristotle wrote over 2,000 years ago, Nicomachean Ethics. According to Aristotle, a virtuous citizen must be educated. Without virtues (άρετή) – at least a certain degree of virtues – the polis community is impossible. Virtues are the human properties or action dispositions which facilitate the existence of telos, the purpose of a human being.” The telos of a man is to live a life worth living (eudaimon). Man achieves his telos by living a good life, which is a life lived according to certain virtues. In this article we consider what kind of a person a virtuous teacher is and what kind of a friend she is to her pupils.